Navigating Economic Turbulence: Marketing Strategy Innovations for MSMEs - Nia Sonani (Escalate : Economics and Business Journal, 2025)
This study explores the adaptation of marketing strategies by micro, small, and medium-sized enterprises (MSMEs) in Padang during an economic crisis. The research examines how these businesses have navigated the challenges posed by reduced consumer spending, market uncertainty, and supply chain disruptions. Through qualitative methods, including in-depth interviews, observation, and document analysis, the study identifies key strategies employed by MSMEs, such as digital marketing, product adaptation, and promotional activities. The findings show that MSMEs were able to maintain customer engagement and drive sales by leveraging digital platforms and adjusting their product offerings to meet the needs of price-sensitive consumers. However, challenges such as limited digital literacy, financial constraints, and increased competition were also identified as significant barriers to the effective implementation of these strategies. The study concludes that while MSMEs in Padang demonstrated resilience through adaptive marketing approaches, additional support in digital skills development and resource allocation is needed to enhance their competitiveness in future crises. The research contributes to the understanding of how MSMEs can adapt their marketing strategies during economic downturns and provides recommendations for both businesses and policymakers to improve resilience in the face of ongoing economic challenges.